Positive effects of communal coping in the aftermath of a collective trauma: The case of the 2010 Chilean earthquake (European Journal of Education and Psychology, 2018)
A cross-sectional study examines the relationship between participation in secular demonstrations, spiritual rituals, and communal coping, as well as the question whether these strategies might serve as triggers of post-traumatic growth, and enhance social well-being. A communal coping scale, showing satisfactory structural validity, was administered to a quasi-random sample (N = 517) of people affected by an earthquake in Chile in 2010. The results indicated that adaptive forms, such as communal reappraisal, regulated emotional expression, communal distraction, and communal searching for social support, were associated with social well-being (SWB) and post-traumatic growth (PTG). Participation in spiritual rituals was specifically related to communal reappraisal and contributed to post-traumatic growth. On the other hand, participation in secular collective gatherings also reinforced post-traumatic growth, as well as social well-being, but not through communal reappraisal. Overall, this study confirmed social functions of collective ritualized activities, which through the reinforcement of in-group interaction, foster individual post-traumatic growth and social well-being of people affected by a collective trauma, like an earthquake. Results are discussed in the framework of a collective positive psychology approach on micro- and macro-social processes of coping and their implications for social well-being.